Putative Role of the Kisspeptin/Kiss1R System in Promoting Hypothalamic GnRH Release, Pubertal Maturation, and Regulation of Ovulation Considering the Central Reproductive Axis - Haroon Latif Khan; Shahzad Bhatti; Zirva Sehole; Hooria Younas; Sammar Nathaniel; Sana Abbas; Celal Kaloglu; Rachel Ziders; Aysegul Yildiz; Ahmed M. Isa (Fertility & Reproduction, 2022)
Kisspeptin is a class of neuropeptides that are the product of the Kiss1 gene. These neuropeptides play an important role in maintaining gonadotropin-releasing hormone (GnRH) levels and their release through hypothalamic neurons. Subsequently, they also play an important role in maintaining gonadotropin levels, as GnRH levels stimulate the release of follicle-stimulating hormone (FSH) and luteinizing hormone (LH), which allow induction of gametogenesis of pubertal maturation. The importance of the Kiss1 gene in reproduction became evident when natural mutations in this gene were discovered, which were associated with hypothalamic hypogonadism (HH) and delayed puberty. Kisspeptin and its KISS1R receptors are expressed in the mammalian ovary. The putative role of the Kisspeptin system in the ovary directly controls oocyte maturation, follicular development, and ovulation in an autocrine and paracrine fashion. These essential facts of kisspeptin and its receptor are necessary to maintain the central reproductive axis.